The Influence of Transformational Leadership and Work Motivation on Police Personnel Performance Mediated by Work Discipline - Satriya, Ifan Bagus; Suswati, Endang; Mulyono, Sugeng; Haritsar, Yosar (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study explores the influence of transformational leadership and work motivation on employee performance, emphasizing the mediating role of work discipline. Transformational leadership refers to a leader’s ability to inspire, encourage, and motivate members to achieve optimal performance and continuous improvement. The objectives of this research are sevenfold: (i) to analyze the influence of transformational leadership on performance, (ii) to examine the effect of work motivation on performance, (iii) to assess the relationship between transformational leadership and work discipline, (iv) to determine the influence of work motivation on work discipline, (v) to evaluate the effect of work discipline on performance, (vi) to investigate how transformational leadership impacts performance through work discipline, and (vii) to explore how work motivation affects performance through work discipline. The study adopts a descriptive quantitative approach, involving 300 police personnel as respondents. Sampling was conducted using the Slovin formula with proportional random sampling to ensure balanced representation across strata or regions. Data were analyzed using the Partial Least Squares (PLS) method. The results indicate that transformational leadership and work motivation both have a positive and significant effect on performance. Work discipline also plays a vital role in enhancing performance directly. Additionally, work motivation significantly contributes to improving work discipline. The findings further reveal that transformational leadership indirectly improves performance through the mediating effect of work discipline. Overall, the study underscores the importance of transformational leadership and motivation as key drivers in fostering disciplined behavior and optimizing employee performance within law enforcement organizations.